Immunizations under sedation at a paediatric hospital in Melbourne, Australia from 2012–2016. Issue 25 (14th June 2018) - Cheng, Daryl R.; Elia, Sonja; Perrett, Kirsten P.
Highlights: This article summarizes the effective use of sedation techniques for special groups undergoing pediatric vaccination. Sedation for immunizations is of particular importance in a subset of pediatric patients with anxiety disorders and developmental disorders. There is currently no best practice guideline for sedation during immunization in this pediatric subgroup. For this subset of patients, specific easily administered distraction and sedation techniques enable immunizations to be given effectively. Abstract: Background: Sedation for immunizations is of particular importance in a subset of paediatric patients with anxiety disorders, needle phobia, developmental or behavioural disorders. The Royal Children's Hospital (RCH) Melbourne offers a unique immunization under sedation service for these patients. We aimed to evaluate the number and types of patients using inpatient sedation for immunizations, distraction and sedation techniques used, and outcomes of these procedures. Methods: A medical record review was conducted on all patients who had immunization under sedation between January 2012 to December 2016 in the RCH Day Medical Unit (DMU). Results: A total of 139 children and adolescents had 213 vaccination encounters. More than half of the vaccination encounters involved multiple vaccines. A total of 400 vaccines were administered. One third of patients (32.3%) had multiple DMU admissions for vaccinations. The median age of patients was 13 years. There were only 10 (4.7%) failed attempts at vaccination; all due to patient non-compliance with prescribed sedation. The majority of patients (58.9%) had a diagnosis of needle phobia. Sedation was most commonly adequately achieved with inhaled nitrous oxide (54.7% sole agent). Midazolam was often used as an adjunct therapy (42.8%). Local anaesthetic cream or play therapy, were used in only 5.9% and 3.9% of patients respectively, although this may reflect poor documentation rather than actual practice. Conclusions: For a subset of paediatric patients for which standard immunization procedures have failed, distraction techniques and conscious sedation enable immunizations to be given safely and effectively. Future research will develop protocols to streamline immunization procedures under sedation.